Parkinson's disease patients with bilateral subthalamic deep brain stimulation gain weight - Macia, Frédéric; Perlemoine, Caroline; Coman, Irène; Guehl, Dominique; Burbaud, Pierre; Cuny, Emmanuel; Gin, Henri; Rigalleau, Vincent; Tison, François (Movement disorders, 2004)
Weight, body mass index (BMI) and energy expenditure/energy intake (EE/EI) was studied in 19 Parkinson's disease (PD) patients after subthalamic deep brain stimulation (STN‐DBS) versus 14 nonoperated ones. Operated patients had a significant weight gain (WG, + 9.7 ± 7 kg) and BMI increase (+ 4.7 kg/m2). The fat mass was higher after STN‐DBS. Resting EE (REE; offdrug/ON stimulation) was significantly decreased in STN‐DBS patients, while their daily energy expenditure (DEI) was not significantly different. A significant correlation was found among WG, BMI increase, and pre‐operative levodopa‐equivalent daily dose, their reduction after STN‐DBS, and the differential REE related to stimulation and the REE in the offdrug/OFF stimulation condition. In conclusion, STN‐DBS in PD induces a significant WG associated with a reduction in REE without DEI adjustment. © 2003 Movement Disorder Society